Oil in the coronavirus whirlwind - Kasim Asker Hasan (Universidad Central de Venezuela, 2021)
By the seventh decade of the 20th century, the world was divided into two large blocks: the Western one, which complemented the satisfaction of its energy needs with imports from the Middle East; subjected to the tensions between the hegemonic pretensions of the socialist world and the dominance of the financial system centered on the Bretton Woods agreements, creators of the IMF and the World Bank. The increase in oil prices in the eighth decade, due to the appetite of China and the desire to improve the material well-being of the countries of the Middle East, created incentives and pressures to introduce modifications in the world monetary order and in its political components basic: the National States; situations whose preliminary analysis is the purpose of this essay Keywords: Petroleum; coronavirus; middle East